PROTOTYPE MONITORING SISTEM INFORMASI METEOROLOGI PENERBANGAN BERBASIS MIKROKONTROLLER SEBAGAI MEDIA PEMBELAJARAN DI POLTEKBANG MEDAN - eriansyah saputra hasibuan (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2020)
In the field of aviation, the need for weather and climate information is very much needed. Weather and climate information is very helpful for aviation safety. Therefore an upgrade is needed to provide accurate and fast data. In developing this effort, the researchers conducted an information system design with a control system using a Node MCU V3 microcontroller. The sensor used in this research uses a DHT22 sensor for temperature and humidity sensors, BMP180 sensor for air pressure sensor, Anemometer Cup JL-FS2 for wind speed sensor and RS485 for cardinal direction sensor. ESP8266 used to send observation data from the design tool to web monitoring. The result of design was a monitoring system for temperature, relative humidity, cardinal pressure and wind speed providing an accuracy correction of -1.4 to 2.10C for air temperature data, correction accuracy of 2.4 to 5.9% RH for humidity data, correction accuracy -1.6 to 1.3 for air pressure data, for data wind directions have a measurement standard error of 32.4%, for eye direction data, and accuracy correction -1.6 to 2.3 knots for data wind speed.